2011
DOI: 10.1371/journal.pone.0019551
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference Underlies the Contraction Bias in Delayed Comparison Tasks

Abstract: Delayed comparison tasks are widely used in the study of working memory and perception in psychology and neuroscience. It has long been known, however, that decisions in these tasks are biased. When the two stimuli in a delayed comparison trial are small in magnitude, subjects tend to report that the first stimulus is larger than the second stimulus. In contrast, subjects tend to report that the second stimulus is larger than the first when the stimuli are relatively large. Here we study the computational prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
193
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(230 citation statements)
references
References 23 publications
14
193
0
Order By: Relevance
“…The CAM is similar to other Bayesian models that have been used to explain biases in memory for size estimation (Ashourian & Loewenstein, 2011), time perception (Jazayeri & Shadlen, 2010), and hue bias Olkkonen, McCarthy, & Allred, 2014). Research has found these effects extend to judgments of realistic and familiar objects (Hemmer & Steyvers, 2009a, 2009b.…”
mentioning
confidence: 63%
“…The CAM is similar to other Bayesian models that have been used to explain biases in memory for size estimation (Ashourian & Loewenstein, 2011), time perception (Jazayeri & Shadlen, 2010), and hue bias Olkkonen, McCarthy, & Allred, 2014). Research has found these effects extend to judgments of realistic and familiar objects (Hemmer & Steyvers, 2009a, 2009b.…”
mentioning
confidence: 63%
“…4A). Poor performance might be explained by "contraction bias," which posits that during the interstimulus delay, the neuronal representation of σ base drifts toward the expected value, or "prior," of all base stimuli presented in recent history (42,43). † By this account, on low-σ base trials, the representation of σ base shifted in the upward direction, toward the mean σ base of the complete SGM.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian priors are expected to apply to the perceptual appearance of stimuli, even in view. In perceptual contexts, Bayesian models have successfully explained stimulus-specific patterns of bias 53 in many domains, including size (Ashourian & Loewenstein, 2011), time (Jazayeri & Shadlen, 2010), motion speed (Stocker & Simoncelli, 2006), and orientation (Girshick et al, 2011 …”
Section: Categories As Priorsmentioning
confidence: 99%